The effect of smartphone dependence on learning burnout among undergraduates: the mediating effect of academic adaptability and the moderating effect of self-efficacy - Chen, Chunmei; Shen, Yuanyi; Xiao, Fanghao; Ni, Jianchao; Zhu, Yujie (Frontiers in Psychiatry, 2023)
Mobile phone dependence is closely related to the physical and mental health development of college students and their learning. The purpose of this study was to explore the relationship between mobile phone dependence, academic adaptability, self-efficacy and learning burnout among college students and its underlying mechanisms. The study was conducted on 2110 college students using the Mobile Phone Dependence Scale, the College Student Learning Adjustment Scale, the College Student Learning Burnout Scale and the Self-Efficacy Scale to develop a mediation model and a moderation model. The results showed that (1) mobile phone dependence significantly negatively predicted academic adaptability; (2) academic adaptability significantly negatively predicted learning burnout; (3) mobile phone dependence significantly positively predicted learning burnout; (4) academic adaptability partially mediated the effect of mobile phone dependence on learning burnout; (5) self-efficacy played a moderating role in the effect of academic adaptability on learning burnout. These findings can help researchers and educators better understand the underlying mechanisms between mobile phone dependence and learning burnout. Meanwhile, the findings can provide practical and effective operational suggestions for preventing and intervening in college students' learning burnout and improving their academic adaptability.